THE IMPLEMENTATION OF WORD SEARCH PUZZLE GAMES IN TEACHING SPEAKING AT TENTH GRADE OF NURUL FATA SENIOR HIGH SCHOOL - Shofi Fathoni; Dinar Vincy YB (Universitas Suryakancana, 2026)
The focus of this research is speaking learning used by tenth grade students at Nurul Fata High School and what problems are faced in tenth grade at Nurul Fata High School. There are two problems in this research. First, how to apply word search puzzle games in teaching speaking. Second, how do students respond to word search games in teaching speaking. This research aims to determine the application of word search puzzle games in teaching speaking and to determine students' responses to word search games in teaching speaking.This research uses a qualitative approach with descriptive research type. The research obtained data by means of interviews, observation, documentation. The informants for this research were subject teachers and tenth grade students. Meanwhile, to check the validity of the data using data triangulation and method. Results of research on the application of word search games stimulate students with questions related to the subject matter to be studied. The teacher makes small boxes on the blackboard so that they form a square or rectangle. The teacher fills in hundreds of letters. Then the words are hidden in letters. Students are formed into several groups. Ask students to observe the words. Order students to memorize words. Meanwhile, students' responses to word search games the students' response to the word search puzzle game in teaching speaking was that students were more enthusiastic and active in participating in the lesson and also found it easier to remember what they had learned and it was even easier for students to pronounce it. until they memorize the vocabulary they find.Key word: Puzzle game, speaking,